INTERNALISASI WAWASAN BAHARI DALAM PEMBELAJARAN SEJARAH MATERI POKOK KEDATANGAN BANGSA BARAT STUDI KASUS SMA N 1 KENDAL (Forum Ilmu Sosial, 2015)
This study aims to determine the internalization of nautical knowledge in the subject matter of the arrival of the west of the teaching of history in SMA Negeri 1 Kendal. In developing the nautical minded character education, awareness of who he was and his people is an important part. This study uses qualitative research with case study design. The research data obtained by using sheets of observations, interviews, questionnaires, and evaluation. The results showed that a history teacher at SMA Negeri 1 Kendal integrating values (honesty, discipline, confidence, responsibility, daring, cooperate and respect the opinion) to the character nautical insight into the learning process .. The results of the questionnaire, get a percentage score enough, with the percentage amount of between 41%